Microwave-assisted synthesis, photocatalysis and antibacterial activity of Ag nanoparticles supported on ZnO flowers - Anukorn Phuruangrat (2018)
© 2018 Elsevier Ltd ZnO flowers with different Ag contents were successfully synthesized by a simple microwave method. Phase and morphologies of heterostructure Ag/ZnO composites were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. The results showed that heterostructure Ag/ZnO composites were composed of face centered cubic Ag supported on hexagonal ZnO flowers of hexagonal prism nanorods with 100 nm wide and about 2–3 μm long, including the detection of Ag 3d5/2 and Ag 3d3/2 for metallic Ag of 10 wt% Ag/ZnO composites. The photocatalytic activity of heterostructure Ag/ZnO composites was evaluated through photodegradation of methylene blue under UV light. Escherichia coli DH5α (gram-negative bacteria) and Stapphylococcus aureus ATCC 25923 (gram-positive bacteria) were used to test for antibacterial activity. The 10 wt% Ag/ZnO composites showed the best performance for photocatalysis and had the antibacterial activity.